The Marketing Strategy During Covid 19 Pandemic at Hotels in Parapat Area, Simalungun Regency, North Sumatera, Indonesia - Yon Suprapto (Politeknik Pariwisata Medan, 2021)
COVID-19 pandemic is a very rare disease and greatly affects the world of tourism in general and the world of hospitality in particular. The way that is used to be has totally changed. The number of guests decreased drastically due to the restrictions (lockdown) as well as the implementation of health protocols implemented in our country. Parapat, which is known as a city that is always full of tourists, now facing a new problem dealing with the coming of tourists. The hotel occupancy rate immediately dropped drastically. Many room reservations have been cancelled. For this reason, the researcher took the title of marketing strategy in this COVID-19 pandemic. What is being done is that the owner should take an action and the marketing department continues to work hard to find ways to keep hotel survived. These various strategies are important to do because they involve hotel operations and also the save the hotel workers not to be jobless. A positive market response is the result of a marketing strategy that is acceptable to the market. The research method used is a qualitative way by conducting interviews with informants. The conclusion obtained is that the hotel is able to overcome the problem of reducing guests during this covid 19. Therefore the strategies happened in Parapat could be implemented as a model to be applied in other areas or by making changes in the form of adaptation in other areas.